Efforts to Maintain Residents Environmental Health through Socialization of Therapeutic Parks in Cempaka Putih Timur Village, Central Jakarta - Hinijati Widjaja; Rini Fitri; Herika Herika; Rully Besari Budiyanti (Fakultas Pertanian, Universitas Samudra, 2022)
The environmental health of residents in Cempaka Putih Timur Subdistrict, Central Jakarta, can be improved by managing a therapeutic garden. Residents are taught the knowledge and understanding to plant therapeutic value plants overlooking their gardens and yards. This community service aims to increase the awareness and knowledge of residents about the importance of managing therapeutic gardens in home yards. Implementing this community service activity begins with the stages of socialization and discussion about overlooking the yard with a therapeutic garden. This community service increased the knowledge and awareness of residents in the Cempaka Putih Timur Subdistrict, Central Jakarta, about the importance of a therapeutic garden. Suggestions for residents in Cempaka Putih Timur Subdistrict, Central Jakarta, to manage their respective yards as therapeutic gardens and increase their knowledge about the use of therapeutic gardens as a place of comfort (healing) in maintaining environmental health.